2010
DOI: 10.1148/radiol.10092377
|View full text |Cite
|
Sign up to set email alerts
|

Atrial and Ventricular Functional and Structural Adaptations of the Heart in Elite Triathletes Assessed with Cardiac MR Imaging

Abstract: Changes in cardiac morphologic characteristics and function in elite triathletes, as measured with cardiac MR imaging, reflect a combination of eccentric and concentric remodeling with regulative enlargement of atrial and ventricular chambers. These findings are different from what has been observed in previous studies in other types of elite athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 40 publications
7
38
5
2
Order By: Relevance
“…In line with previous studies, athletes have larger left atrial volumes compared to gender matched controls (6)(7)(8). Furthermore, this study shows that right atrial volumes increase with increasing fitness.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous studies, athletes have larger left atrial volumes compared to gender matched controls (6)(7)(8). Furthermore, this study shows that right atrial volumes increase with increasing fitness.…”
supporting
confidence: 92%
“…Few studies have investigated the effects on atrial volumes. Using echocardiography and cardiac magnetic resonance imaging (CMR), recent studies have shown increased atrial dimensions and volumes in endurance athletes (6)(7)(8). However, studies of atrial adaptation to training in women are scarce and data on the effects on right atrial volumes in both men and women is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The most frequently used quantification technique for LV volumetric analysis is ECG-gated, segmental balanced steady-state free precession cinegraphic imaging, which gives excellent blood-tissue differentiation without any contrast. 23,24 LV volumes are evaluated by applying the Simpson rule, using a series of shortacting images obtained with a slice thickness of 6-8 mm.…”
Section: D and 3d Echocardiographymentioning
confidence: 99%